Biomarkers of oxidative stress in the fetus and newborn (Hematology Meeting Reports, 2009)
Oxidative stress presents numerous opportunities for tissue injury through formation of reactive oxygen/nitrogen species. It is becoming more evident that oxidative stress is the final common endpoint for a complex convergence of events, some genetically determined and some triggered by an in utero stressor. Oxidative stress affects a complex array of genes involved in inflammation, coagulation, fibrinolysis, the cell cycle, signal trasduction and programmed cell death. It quickly becomes clear that a single pathway may be insufficient to provide clarification of oxidative stress action in the patogenesis of the so-called free radical diseases of the newborn.